A Mineralogical Approach to Auriferous Arsenopyrite - Graham J (The Australasian Institute of Mining and Metallurgy, 1992)
The successful processing of arsenopyritic ores is difficult and will be facilitated by a better understanding of the mineralogy of gold within arsenopyrite and the type of arsenopyrite in which gold is taken up. Solid solution gold in arsenopyrite is now well documented, and is a significant cause of refractory behaviour in gold processing. Investigations of the crystal structure and stoichiometry of arsenopyrite by X-ray diffraction, electron microprobe analysis and convergent beam electron microscopy have been carried out in order to understand how the gold is incorporated into the structure. Variations in stoichiometry, particularly the As:S ratio, of arsenopyrite leads to variations in structural parameters. These variations result in slight changes in thermal behaviour. The distribution of invisible gold in an arsenopyrite grain is generally non-uniform and synthesised samples contain up to 2 wt per cent gold. A transmission electron microscopy (TEM) technique called ALCHEMI is being used to identify the substitution site. The process of gold agglomeration together with evidence of an ordered breakdown of arsenopyrite to pyrrhotite has been documented with the use of TEM. An arsenopyrite grain containing invisible gold was heated with an electron beam resulting in recrystallisation of arsenopyrite to pyrrhotite with arsenic being expelled. The gold is mostly insoluble in the pyrrhotite lattice and therefore exsolves out and combines with other gold atoms to form droplets at the boundary of the pyrrhotite.